Investigation of interdependence between touch and sight - Kaffemanas, R. (Psichologija, 1991)
The article presents the data of the experimental investigation of the interdependence between schoolchildren’s touch and sight. The peculiarities of intermodal transference of information, the differences between touch and sight perception have been analysed. It has been stated: having, joined the two analysers – the sight and the touch – in the process of perception the results of perception in many cases are much better.